2009
DOI: 10.1192/bjp.195.52.s13
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacology and adverse effects of antipsychotic long-acting injections: A review

Abstract: Dosing of LAIs is complicated by delayed release of drug, changes in plasma levels without change in dose, and by the lack of data establishing clear dose requirements. All LAIs offer the prospect of assured adherence (although patients may still default on treatment) but their use is complicated by adverse effects, complex pharmacokinetics and confusion over dose-response relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 73 publications
(112 reference statements)
1
82
0
7
Order By: Relevance
“…Usually, medication-naïve individuals are acutely sensitive to APs in terms of responsiveness as well as side effects [Kelly et al 2005;Alvarez-Jiménez et al 2008;Francey et al 2010] including extrapyramidal symptoms (EPS) [Chatterjee et al 1995] and weight gain [Strassnig et al 2007]. However, it is generally admitted that LAIs have a more acceptable side effect profile in comparison with their oral counterparts due to lower variation in peak and trough levels, and any concerns over debilitating side effects may be due to dosing errors [Taylor, 2009].…”
Section: Guidelines and Recommendations For The Treatment Of Schizophmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, medication-naïve individuals are acutely sensitive to APs in terms of responsiveness as well as side effects [Kelly et al 2005;Alvarez-Jiménez et al 2008;Francey et al 2010] including extrapyramidal symptoms (EPS) [Chatterjee et al 1995] and weight gain [Strassnig et al 2007]. However, it is generally admitted that LAIs have a more acceptable side effect profile in comparison with their oral counterparts due to lower variation in peak and trough levels, and any concerns over debilitating side effects may be due to dosing errors [Taylor, 2009].…”
Section: Guidelines and Recommendations For The Treatment Of Schizophmentioning
confidence: 99%
“…That said, appropriate prescribing and dosing of LAIs is complicated by their long half-lives, delayed release (up to 28 days in the case of risperidone) and risk of postinjection delirium/sedation syndrome (olanzapine pamoate) [Novakovic et al 2013]. Lack of clear dose-response data lead clinicians to approximate dosing in their clinical practice; even where fixed-dose studies have established 'dose-response' curves, there is debate regarding the clinical value of doses at the higher and lower end of the dose range [Taylor, 2009]. The pharmacokinetic and clinical characteristics of most commonly used LAI APs are described in Table 1.…”
Section: Bioavailability and Dosing Of Lai Apsmentioning
confidence: 99%
“…However, the second-generation antipsychotics lack an alcohol (-OH) terminal suitable for esterification and present a different release mechanism. The dissemination thus occurs mainly by encapsulation of the drug into a degradable polymer (risperidone) and injection of a suspension of drug compound (olanzapine) [19]. The peak concentration of olanzapine pamoate is achieved in four days with a half-life of 26 days.…”
Section: Discussionmentioning
confidence: 99%
“…2 There is a widespread belief that LAIs have more and even worse adverse effects than their equivalent oral preparations. Although there is support for this notion in the literature, 3 a recent review of randomized controlled studies has shown that, whereas some of the LAIs currently available may cause similar or more severe side effects, others such as risperidone have similar or even milder side-effect profiles than their oral counterparts. 4 In addition, because LAIs have been used over the past 50 years, many psychiatrists consider that they are ''old-fashioned'' drugs.…”
mentioning
confidence: 93%